EXAMINING THE EFFECT OF SERVICE QUALITY DIMENSIONS ON CUSTOMER SATISFACTION IN WESTERN THEMED RESTAURANTS - Wan Ahmad Reza Wan Zainuddin; Aida Khalida Mohamed Idris; Ashraf Siddik Khan Abd Rahim Siddiqe; Hasniza Abdullah; Farhan Faat (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The goal of the study is to comprehend how customer contentment in Western themed restaurants is influenced by service quality. Research on numerous service dimensions has resulted from this. Respondents are chosen by random selection from a range of demographic groupings. The data are gathered quantitatively, and questionnaires are given to respondents before a random sample is chosen for analysis. A survey was completed by 150 participants, from a total of 200 questionnaires distributed and the respondents have answered all 30 questions. Findings show a substantial correlation between service quality and patron satisfaction in the restaurant industry (tangibles, assurance, responsiveness, reliability, and empathy). This study is specifically carried out in Shah Alam, Malaysia, in order to get fruitful results. The time frame for this research were carried out from end of June 2022 up till early February 2023.The findings will benefit investors, present restauranteurs and entrepreneurs by adding to the body of knowledge in the fields of strategic marketing, entrepreneurship and customer service.